Sustainability evaluation of alkali-activated mortars incorporating industrial wastes. (2021) - Joudah, Zahraa Hussein; Huseien, Ghasan Fahim; Samadi, Mostafa; Shukor Lim, Nor Hasanah Abdul
Abstract: In this study, the alkali activated mortars (AAMs) were synthesized from waste ceramic tile powder (WCP), ground blast furnace slag (GBFS) and fly ash (FA). The effects of binder composition on the sustainability of AAMs were investigated. GBFS was replaced by FA at different percentages of 10%, 20%, 30%, and 40%. In contrast, the WCP content of the binders was kept at 50% in all AAMs. Engineering properties like compressive strength, drying shrinkage and sulfuric acid resistance were evaluated in this study. From the study, the compressive strength of proposed mortar was found to be decreased with a higher content of FA in the alkali-activated matrix. Besides, AAMs with a higher content of FA demonstrated a lower drying shrinkage and better performance under sulfuric acid environments. Other than enhanced durability properties, a lower energy consumption, smaller carbon dioxide emissions, and cheaper production cost of proposed mortars were shown when GBFS was replaced by FA.